1990
DOI: 10.1017/s0272263100009062
|View full text |Cite
|
Sign up to set email alerts
|

Functionalism in Second Language Acquisition

Abstract: This article examines the role played by functional approaches to linguistics in understanding second language acquisition (SLA). Central premises and tenets of functional approaches are described, and several key theoretical problems with functional efforts are detailed. The problem of referential management (the selection of nominal vs. pronominal NPs) in second language discourse production is examined. The general conclusions are drawn that (a) functional approaches to linguistics have a significant role t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
6

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 65 publications
(66 reference statements)
0
20
0
6
Order By: Relevance
“…A major assumption Chomsky makes is that the linguistic input to children acquiring their first language underdetermines or is insufficient to account for language acquisition. Moreover, children 5 Some of the more prominent among these being Krashen's monitor model (1985), Hatch and Hawkins' experiential approach (1985); Bialystok and Ryan's knowledge and control dimensions (1985); McLaughlin's cognitive theory (1987); the multidimensional model (Pienemann & Johnston, 1987;Clahsen, 1987); Andersen's cognitive interactionist model (1988), and the functionalist perspective (Tomlin, 1990).…”
Section: Nativist Universal Grammar (Ug)mentioning
confidence: 99%
“…A major assumption Chomsky makes is that the linguistic input to children acquiring their first language underdetermines or is insufficient to account for language acquisition. Moreover, children 5 Some of the more prominent among these being Krashen's monitor model (1985), Hatch and Hawkins' experiential approach (1985); Bialystok and Ryan's knowledge and control dimensions (1985); McLaughlin's cognitive theory (1987); the multidimensional model (Pienemann & Johnston, 1987;Clahsen, 1987); Andersen's cognitive interactionist model (1988), and the functionalist perspective (Tomlin, 1990).…”
Section: Nativist Universal Grammar (Ug)mentioning
confidence: 99%
“…These findings are relevant if the overuse of full NPs and the overuse of pronouns are manifestations of the same phenomenon. Tomlin (1990), using an experimental on-line production task, elicited narratives from NNSs of English. He found that the speakers used mostly full NPs and that changes in "activated memory," a factor affecting NSs' choice of nominal, did not have any relation to whether NNSs used a pronoun or full NP.…”
Section: Previous Research On Nominal Referencementioning
confidence: 99%
“…Also, the study of second language from the functional perspective begins with the assumption that the purpose of language is communication, and that development of linguistic knowledge (be it in First or Second Language) requires communicative use. Finally, the scope of concern goes beyond the sentence to include discourse structure and how language is used in interaction, and to include aspects of communication beyond language (see also , Tomlin 1990). Tomlin (1990, p155) admits that the functional approach "represents a comprehensive orientation to matters of language use and interaction which underlie and affect the temporal acquisition of second languages".…”
Section: Introductionmentioning
confidence: 99%